Telemedicine: challenges to dissemination in Brazil - Jose Manuel Santos de Varge Maldonado; Alexandre Barbosa Marques; Antonio Cruz
Abstract: Telemedicine has been seen as an important tool for facing the challenges of universal health systems. The goal of this article is to discuss the main challenges to its full dissemination in Brazil. Being a somewhat new area, there are not many scientific papers that systematize it. This article is an exploratory paper, as it aims to provide an overall perspective on the subject. From an economic point of view, telemedicine is a strategic area due to its an intrinsic potential of being a source for generating innovation, for requiring and incorporating technological breakthroughs from other areas, and for its interdisciplinary nature and dynamic inter-relations that drive different industries. From the social perspective, it has the potential to make access to health services democratic, by connecting remote regions with health services located in hospitals and centers of reference for prevention, diagnosis and treatment.